Evolving developments in grid and cloud computing : advancing research - Udoh, Emmanuel , 1960- (Information Science reference, 2012)
"This book contains investigations of grid and cloud evolution, workflow management, and the impact new computing systems have on education and industry"-- Provided by publisher